An exploration of internal communication dimensions and transformational leadership to improve employee advocacy: a study based on an employee perspective in China’s broadcasting stations - Dong, Shaochen; Ramli, Romlah; Cheah, Joyce Lynn-Sze (Frontiers in Communication, 2025)
IntroductionEmployee advocacy (EA) has become an essential organisational behaviour, remarkably reflecting its influence on companies’ internal and external perceptions. Notwithstanding its significance, limited research subsists on the drivers of EA, especially in non-Western backgrounds such as China. The purpose of this study is to explore whether transformational leadership (TL) and internal communication dimensions (ICD), including transparent communication (TC) and symmetrical communication (SC), can improve employee advocacy (EA) in China’s television broadcasting stations (CTBS).MethodsA qualitative research design was used, and semi-structured interviews were conducted with 30 employees from a CTBS in Shandong province. The data, using thematic analysis supported by ATLAS.ti software, was analysed.ResultsThe findings disclosed that employees reckon the TL and ICD’s importance in improving EA and see employees engagement (EE) as an important prerequisite. Remarkably, EE plays a significant role in mediation, impacting EA. The efficiency of these relations is also hindered due to limited opportunities for professional development, hierarchical structures, and sometimes obstacles in communication practices.DiscussionThe study portrays its contribution to the literature by spotlighting the dynamics and challenges of promoting EA in China’s organisational background. Future research should focus on challenges, taking up these hindrances, and further investigate how to adapt communication strategies for effective leadership in the context of Chinese organisations’ unique cultural and structural landscape.